Q. 43.6( 17 Votes )
Given: sin 𝛳 =
We know that, sin2 θ +cos2 θ =1
⇒ sin2 A = 1-cos2 A
⇒ sin A = √ (1-cos2 A
So, cos 𝛳 = √(1-a2/b2 ) = √((b2-a2)/b2 ) = √(b2-a2 )/b
Hence, the answer is √(b2 - a2 )/b
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation